Behavioral responses of sand fly Nyssomyia neivai (Psychodidae: Phlebotominae) to 1-hexanol and light - Machado, Vicente Estevam [UNESP]; da Rocha Silva, Flávia Benini [UNESP]; Goulart, Thais Marchi; Pinto, Mara Cristina [UNESP] (Elsevier, 2022)
Background: The search for attractive baits that may facilitate the capture of haematophagous insects has been epidemiologically relevant. Sand flies use chemical cues in different phases of their life cycles to find carbohydrate meals, mates, blood meals and oviposition sites. Few studies have related the behaviours of sand flies with volatile compounds that can influence their life cycles. Previous studies in our laboratory have shown that 1-hexanol released on filter paper is a good attractant for the sand fly Nyssomyia neivai, which is suspected in the transmission of the aetiologic agent of American cutaneous leishmaniasis. Methods: In this study, we developed two release systems to modulated 1-hexanol release: system 1 contained gellan gum and pectin (4:1 ratio), 3% aluminium chloride and 1% glutaraldehyde; system 2 contained: gellan gum and pectin (4:1 ratio) and 3% aluminium chloride. After addition of 1-hexanol to each release system, trials were performed in a wind tunnel with Ny. neivai males and females (unfed, blood-fed and gravid) to evaluate activation and attraction responses. Results: Males and unfed females showed the same response pattern to the systems. For both systems, the males and unfed females of the sand flies showed an activation response up to 24 h. The number of responsive gravid females was lower than unfed females for both systems. The blood-fed females showed no responses in any of the release systems. Conclusions: Our findings indicate that the state of the females (unfed, fed and gravid) can interfere with the sand fly responses to volatile compounds. Additionally, both systems evaluated with the compound showed effectiveness for sand fly attraction.
Keywords: 1-hexanol; Attractiveness; Kairomones; Nyssomyia; Release system; Wind tunnel